PENGARUH TINGKAT PENGALAMAN BERWIRAUSAHA, PRODUKTIVITAS DAN INOVASI TERHADAP PENGEMBANGAN USAHA KULIT LUMPIA ( Studi Kasus Pada UMKM Kulit Lumpia di Kelurahan Kranggan Kota Semarang) - Wahyuni, Sri; Pradhanawati, Ari; Hidayat, Wahyu (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
Business development is a situation where a growing business or not be seen from some of the indicators that can be used as a measurement to determine a growing business or not. For every business is different, so different measures used to determine whether a business succeeds or not. Many emerging competitors can improve business development to stay ahead among its competitors. Factors such as the level of experience in entrepreneurship, productivity and innovation also performed can affect the development of the work done.The purpose of this study was to determine the effect of the level of experience in entrepreneurship, productivity, and innovation to the development of the spring roll skin. This type of research is explanatory research, with data collection through questionnaires and interviews. The sampling technique used nonprobability sampling techniques and sample saturated. The sample amounted to 30 UMKM entrepreneurs spring roll skin on skin Lumpia. This study uses quantitative analysis techniques. Quantitative analysis using validity, reliability, simple regression analysis, the coefficient of determination, the significance test (t test) and f test.The results of this study indicate that all variables are partially independent, entrepreneurial experience level variables (X1) effect on business development (Y) of 38.2%, productivity (X2) effect on business development (Y) by 38%, and innovation (X3) effect on business development (Y) of 39.5%.